2023
DOI: 10.1111/pai.13915
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on childhood asthma: Allergens

Abstract: Exposure to inhalant allergens (primarily house-dust mites, cat and dog allergens) is important in the development of allergen-specific sensitization, and if asthma has developed, further allergen exposure may contribute to ongoing symptoms. However, the relationship between allergen exposure and sensitization is complex. To develop allergen-specific sensitization, one needs to be exposed to that allergen. The absence of a consistent, linear dose-response relationship between specific allergen exposures and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 142 publications
0
16
0
10
Order By: Relevance
“…Food‐related allergic reactions decrease with age and are associated with tolerance to common allergenic foods 8 . Later, due to the increase of children's outdoor activities, microbial exposure and some other factors, the positivity of inhaled allergen increased 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food‐related allergic reactions decrease with age and are associated with tolerance to common allergenic foods 8 . Later, due to the increase of children's outdoor activities, microbial exposure and some other factors, the positivity of inhaled allergen increased 9 …”
Section: Discussionmentioning
confidence: 99%
“…8 Later, due to the increase of children's outdoor activities, microbial exposure and some other factors, the positivity of inhaled allergen increased. 9 An analysis of allergen detection of 930 allergic patients (0-85 years old) in Zhangzhou (a city in Southern China) in 2017, 10 an analysis of 731 patients (3-month-old to 85 years old) in Zhengzhou (a city in the middle area of China) in 2018, 11 and an analysis of 11,641 patients (1-month-old to 98 years old) in Beijing (a city in northern China) from 2013 to 2017 12 all showed that the positive rate of inhalation allergen was higher than that of ingestion allergen before. In this study, the sIgE-positive rate of ingestion allergen was significantly higher than that of inhalation allergen.…”
Section: The Potential Reasons For the Significant Difference Observe...mentioning
confidence: 99%
“…Tomando como base lo publicado por Mallol J et al (11) , con un total de 1100 pacientes pediátricos con asma y rinitis, y un intervalo de confianza del 95%, se consideró una n=86 como tamaño de la muestra para la realización de este estudio, cálculo realizado por Epi Info Versión 3.5.4. El estudio fue aprobado por el comité de ética de la Investigación de la FCMUNA.…”
Section: Materiales Y Métodosunclassified
“…Quantifying allergic sensitization instead, by using IgE titre or size of skin test response, can increase specificity both in terms of diagnostic accuracy [16,17] and capacity to predict the persistence of symptoms [18]; however, a significant number of false-positive test results remain [3,4]. Consequently, although asthma is closely associated with allergic sensitization, most current guidelines do not recommend assessing allergic sensitization for asthma diagnosis or monitoring [19 ▪ ]; nonetheless, most physicians caring for asthmatic children consider monitoring allergy and assessment of sensitization status to be of very high or high priority when monitoring childhood asthma [20 ▪▪ ].…”
Section: Introduction: How Is Sensitization Linked To Atopic Diseases?mentioning
confidence: 99%